Expression of growth differentiation factor-5 and bone morphogenic protein-7 in intraocular osseous metaplasia. Issue 7 (17th June 2005) - Toyran, S; Lin, A Y; Edward, D P
Abstract : Background/aims: Intraocular bone is seen in a wide spectrum of ocular disorders. The pathogenetic mechanisms of bone formation in the eye are unclear. Growth differentiation factor-5 (GDF-5), bone morphogenic protein-7 (BMP-7), and transforming growth factor beta-1 (TGF β1) are multifunctional cytokines that have important roles in bone formation. Immunohistochemistry was used to localise GDF-5, BMP-7, and TGF β1 in the human eye to determine their role in intraocular bone formation. Methods: Paraffin embedded sections from human eyes included fetal eyes (n = 5), normal adult eyes (n = 4), eyes with osseous metaplasia (n = 8), and eyes with focal fibrous metaplasia of the retinal pigment epithelium (RPE) without osseous metaplasia (n = 2). Immunohistochemistry was performed using indirect immunofluorescence with antibodies to GDF-5, BMP-7, and TGF β1. The staining intensity was evaluated semiquantitatively in the RPE, retina, ciliary epithelium, and cornea; and analysed statistically. Results: When compared with normal adult eyes, which showed no RPE immunoreactivity, the RPE metaplasia surrounding areas of osseous metaplasia showed mild GDF-5 and moderate BMP-7 (p = 0.004) intracytoplasmic immunoreactivity. In contrast, trace GDF-5 and mild BMP-7 staining was seen in zones of RPE fibrous metaplasia in areas not associated with osseous metaplasia. Mild intracytoplasmic TGF β1 expression was seen in the RPE metaplasia surrounding the bone when compared with adult eyes. Both fetal and adult eyes showed trace to mild GDF-5 and BMP-7 labelling of the non-pigmented ciliary epithelium which was increased in the eyes with osseous metaplasia. In eyes with osseous metaplasia, a significant decrease in GDF-5 and BMP-7 labelling was noted in fetal keratocytes (p = 0.0159 for both antibodies) when compared to adult eyes. Also, a significant decrease in BMP-7 labelling was seen in keratocytes in eyes with osseous metaplasia (p = 0.0162). Conclusions: The increase in GDF-5, BMP-7, and TGF β1 immunoreactivity in zones of RPE metaplasia in eyes with osseous metaplasia suggests that these proteins have an important role in intraocular ectopic bone formation.